1992
DOI: 10.1063/1.106798
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a two-dimensional electron gas in low pressure metalorganic chemical vapor deposited GaN-AlxGa1−xN heterojunctions

Abstract: We have confirmed the presence of a two-dimensional electron gas (2DEG) in a wide band-gap GaN-AlxGa1−xN heterojunction by observing steplike features in the quantum Hall effect. The 2DEG mobility for a GaN-Al0.13Ga0.87N heterojunction was measured to be 834 cm2/V s at room temperature. It monotonically increased and saturated at a value of 2626 cm2/V s at 77 K. The 2DEG mobility remained nearly constant for temperatures ranging from 77 to 4.2 K. Using Shubnikov–de Haas (SdH) measurements the two-dimensional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(85 citation statements)
references
References 17 publications
2
82
1
Order By: Relevance
“…material quality, the effect has only been produced in a handful of materials, with each of them exhibiting distinctive features in the QH regime as a result of their peculiar electronic properties 5,[7][8][9][10][11] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…material quality, the effect has only been produced in a handful of materials, with each of them exhibiting distinctive features in the QH regime as a result of their peculiar electronic properties 5,[7][8][9][10][11] .…”
mentioning
confidence: 99%
“…The high mobility enable us, for the first time, to observe the QH effect in black Page 4 of 15 phosphorus 2DEG. Black phosphorus thus joins the selected few materials 5,7,8,11 to become the only 2D atomic crystal apart from graphene 9,10 having requisite material quality to show QH effect.We constructed the van der Waals heterostructure using the dry-transfer technique described in ref. 31.…”
mentioning
confidence: 99%
“…Since the first demonstration of the existence of a twodimensional electron gas ͑2DEG͒ at the AlGaN/GaN interface in 1992, 1 tremendous progress has been realized 2 in the field of AlGaN/GaN high electron mobility transistors deposited on various substrates by different growth techniques. For example, Gaska et al 3 reached a room-temperature mobility slightly over 2000 cm 2 /V s (n s ϭ1.3ϫ10 12 cm Ϫ2 ) in an Al 0.2 Ga 0.8 N/GaN structure deposited on 6H-SiC substrate by low-pressure metalorganic vapor-phase epitaxy.…”
mentioning
confidence: 99%
“…In 1992, M. Asif Khan et al first reported the observation of a two-dimensional electron gas (2DEG) in MOCVD-grown AlGaN/GaN heterojections with promising electron properties [3]. This news together with the simulation results [4] that predict high peak velocity, high saturation velocity, and high electron mobility in GaN started to make the AlGaN/GaN heterostructures attractive for microwave and millimeterwave devices and thus to spur more investigations to see its potential.…”
Section: Pappermentioning
confidence: 99%
“…In 1992, Asif Kahn et al reported the first confirmation of high-mobility twodimensional electron gas forming in the Ga-face Al x Ga 1-x N/GaN heterostructure [3], which serves as the basis of the epitaxial structure for high electron mobility transistors (HEMTs). Since then, the growth of AlGaN/GaN HEMT epitaxial structures has been intensively studied and advanced on various substrates, including sapphire, SiC, Si and bulk GaN substrates, using growth techniques such as molecular beam epitaxy (MBE) or metalorganic chemical vapor deposition (MOCVD).…”
Section: Epitaxial Structuresmentioning
confidence: 99%